Factors Affecting Menopause Quality of Life in the 45-55 Years Age Group in Indonesia - Nofa Anggraini; Rosita Sari; Sri Hartiningsih; Nursanti Maria; Yuliawati Dewi; Vera Octavia; Arindi Anggraeni; Rina Riyanti (Postgraduate, University of Mataram, 2024)
Menopause, a natural phase in women aged 45-55, is marked by a decrease in estrogen, impacting their quality of life. This study investigates factors influencing menopausal quality of life in Indonesia in 2024, focusing on education, husband's support, peer support, physical activity, and anxiety. Utilizing a cross-sectional design, the research sampled 35 menopausal women aged 45-55 through purposive sampling, using a questionnaire for primary data collection and chi-square tests for analysis. Univariate analysis revealed that 60% of participants had a good quality of life. Factors included low education (55.1%), high husband support (65.7%), high peer support (61.2%), moderate physical activity (56.7%), and anxiety (55.1%). Bivariate analysis demonstrated significant relationships between education (p = 0.000), husband's support (p = 0.000), peer support (p = 0.000), physical activity (p = 0.000), and anxiety (p = 0.011) with menopausal quality of life. The findings suggest that education, support systems, physical activity, and managing anxiety are crucial for improving menopausal quality of life. It is recommended that menopausal women enhance their understanding of menopause through various resources to better adapt and improve their quality of life.